PENGEMBANGAN APLIKASI AR BERBASIS ANDROID UNTUK PENGENALAN TOKOH PAHLAWAN UANG KERTAS INDONESIA - Bachtiar, Andi; Yuliana, Irma (Politeknik Bisnis Indonesia, 2025)
This research focuses on the development of an Android-based Augmented Reality (AR) application to introduce Indonesian national heroes featured on banknotes to sixth-grade elementary school students. The issue addressed is the lack of student interest and limited learning media regarding the history of national heroes, which often results in low engagement and retention. The research aims to enhance students’ historical knowledge and interest through interactive technology. The development method used is the Multimedia Development Life Cycle (MDLC), which includes stages such as concept, design, material collection, assembly, testing, and distribution. The application utilizes Vuforia SDK and Unity 2D as its main development tools, enabling users to scan banknotes and display 2D animations and information of the corresponding national hero. Testing was conducted using black-box testing to evaluate functionality, and user acceptance testing involving students and teachers to assess usability. The results showed that the application successfully functioned as intended and received positive responses from users, indicating improved student engagement and learning outcomes. This study demonstrates that AR-based educational tools can effectively support history learning in a more engaging and interactive way.